Influence of pre-existing inflammation on the outcome of acute coronary syndrome: a cross-sectional study. Issue 1 (12th January 2016) - Odeberg, Jacob; Freitag, Michael; Forssell, Henrik; Vaara, Ivar; Persson, Marie-Louise; Odeberg, Håkan; Halling, Anders; Råstam, Lennart; Lindblad, Ulf
Abstract : Objectives: Inflammation is a well-established risk factor for the development of coronary artery disease (CAD) and acute coronary syndrome (ACS). However, less is known about its influence on the outcome of ACS. The aim of this study was to determine if blood biomarkers of inflammation were associated specifically with acute myocardial infarction (MI) or unstable angina (UA) in patients with ACS. Design: Cross-sectional study. Setting: Patients admitted to the coronary care unit, via the emergency room, at a central county hospital over a 4-year period (1992–1996). Participants: In a substudy of Carlscrona Heart Attack Prognosis Study (CHAPS) of 5292 patients admitted to the coronary care unit, we identified 908 patients aged 30–74 years, who at discharge had received the diagnosis of either MI (527) or UA (381). Main outcome measures: MI or UA, based on the diagnosis set at discharge from hospital. Results: When adjusted for smoking, age, sex and duration of chest pain, concentrations of plasma biomarkers of inflammation (high-sensitivity C reactive protein>2 mg/L (OR=1.40 (1.00 to 1.96) and fibrinogen (p for trend=0.035)) analysed at admission were found to be associated with MI over UA, in an event of ACS. A strong significant association with MI over UA was found for blood cell markers of inflammation, that is, counts of neutrophils (p for trend<0.001), monocytes (p for trend<0.001) and thrombocytes (p for trend=0.021), while lymphocyte count showed no association. Interestingly, eosinophil count (p for trend=0.003) was found to be significantly lower in patients with MI compared to those with UA. Conclusions: Our results show that, in patients with ACS, the blood cell profile and degree of inflammation at admission was associated with the outcome. Furthermore, our data suggest that a pre-existing low-grade inflammation may dispose towards MI over UA.